Effectiveness of TeV gamma-ray observations at large zenith angles with a stereoscopic system of imaging atmospheric Cerenkov telescopes - Konopelko, Alexander; Aharonian, Felix A.; Hemberger, M.; Hofmann, Werner; Kettler, J.; Pühlhofer, Gerd; Völk, Heinrich J. (Journal of physics. G, Nuclear and particle physics, 1999)
The sensitivity of imaging atmospheric Cerenkov telescopes (IACTs) in TeV -ray observations reaches its maximum at small zenith angles (SZAs) ( 30o) which provides the minimum attainable energy threshold of an instrument. However, for a specific telescope site a number of -ray sources, or source candidates, can only be observed at much larger zenith angles (LZAs) ( 60o). Moreover, the observations at LZAs allow us to extend the observation time window for any object seen at SZAs, as well as to enlarge the dynamic energy range of an instrument towards the highest observable energies of -rays. Based on Monte Carlo simulations we present the results on the sensitivity of a stereoscopic system of five IACTs in observations at LZAs. We point out some important parameters of the telescope design which could substantially improve the efficiency of such observations with forthcoming IACT arrays like CANGAROO III, HESS and VERITAS.
Gesehen am 26.11.2020